Development of educational function of university libraries in the border regions of Russia and China (on the example of the Khabarovsk territory and Heilongjiang province) - Olga A. Simonenko; Ekaterina P. Krivtsova (Развитие образования)
The work is devoted to assessing the operating conditions of scientific libraries at regional universities in Russia and China and identifying prospects for cooperation to strengthen their educational function. The study summarizes the experience and data from the authors' participant observation of the activities of large university libraries in the border regions of the two countries. Cases are provided that characterize the activities of libraries of large regional universities – Pacific National University and Harbin Polytechnic University. Guided by regulatory documents and taking into account the main areas of interstate cooperation, libraries of regional universities implement and expand their educational opportunities in the face of increasing challenges. We are talking about the impossibility of isolated development and the presence of a high interest in finding partners abroad. The educational function of the university library includes education, information literacy, self-education and individual learning, as well as communication between subjects of the educational process.